Value at risk modelling for a one-year time horizon : Case: Company X - Mannila, Onni (My University, 2021)
Financial institutions face many challenges arising from changes in market conditions and new regulations. Risk management framework in financial institutions consists of many guidelines and metrics that are designed to help to examine and monitor the overall risks of their operations. Market risk is one of the main sources of risks that financial institutions face on daily basis. Market risk is the total risk arising from its subcategories: interest rate risk, foreign exchange risk, commodity price risk and equity price risk. The aim of the study is to examine Value at risk (VaR) as a market risk metric especially in a one-year time period. VaR measures the maximum loss on a given period on a specific confidence level. VaR does not give information on losses beyond confidence level. Aim of the study is to examine bootstrapping models with different block lengths and different GARCH(1,1) -models in their ability to model underlying risk factors of the hypothetical portfolio in order to calculate VaR for a time horizon of one year. The effect of the chosen risk factors to results are examined as well as the performance of the different models from 29.04.2010 to 31.12.2021. The empirical study of the thesis is done as case study for Company X. The performance of the bootstrapping models and GARCH -models is compared on nine different time periods in the chosen time frame. The models are being tested against rolling backtesting windows constructed from the hypothetical portfolio values over time. All of the models perform quite similarly throughout time periods and across confidence levels: 99.9%, 99%, 95% and 90%. Bootstrapping with block length of 1 performs better than other bootstrapping models as it has the smallest number of market risk underestimations. EGARCH and TGARCH perform better than other GARCH -models. All of the models have larger amount aggregated breaches than it would be statistically allowed on confidence levels 99%, 95% and 90%.

Rahoituslaitokset kohtaavat jatkuvasti uusia haasteita muuttuvien markkinaolosuhteiden ja uusien regulaatioiden myötä. Riskienhallinnan viitekehys rahoituslaitoksissa sisältää monia ohjenuoria ja mittareita, jotka on suunniteltu auttamaan hallitsemaan ja monitoroimaan liiketoiminnan kokonaisriskejä. Markkinariski on merkittävä riski, jota rahoituslaitosten on päivittäin valvottava. Markkinariski kumpuaa sen alakategorioista: korkoriskistä, valuuttariskistä, hyödykkeiden hinnanmuutoksista ja osakkeiden hinnanmuutoksista. Tutkielman tavoitteena on tarkastella Value at risk -mittaria (VaR) markkinariskin mittaamisessa, etenkin yhden vuoden aikajänteelle. VaR kertoo maksimaalisen tappion tiettynä periodina tietylle luottamustasolle. VaR ei ota kantaa tappioihin luottamustason ulkopuolella. Tutkielman tavoitteena on tutkia bootstrapping -malleja eri pituisilla lohkojen pituuksilla sekä erilaisia GARCH(1,1) -malleja, etenkin niiden kyvyssä mallintaa portfolioon valittuja riskifaktoreita VaR:in laskemiseksi yhden vuoden aikaperiodille. Valittujen riskifaktorien vaikutuksia tuloksiin sekä ja mallien suoriutumista tutkitaan aikaperiodilla 29.04.2010 - 31.12.2020. Empiirinen tutkimus on tehty tapaustutkimuksena Yritys X:lle. Bootstrapping -mallien ja GARCH -mallien suoriutumista vertaillaan yhdeksällä eri aikaperiodilla edellä mainitulla aikavälillä. Mallien suoriutumista tarkastellaan vertaamalla niitä hypoteettisen portfolion historiallisista arvoista laskettuihin lukuihin. Kaikki mallit suoriutuvat samankaltaisesti eri periodeilla sekä eri luottamustasoilla (99.9%, 99%, 95%, 90%). Bootstrapping -malli yhden lohkon pituisena suoriutuu paremmin kuin muut bootstrapping - mallit, sillä sillä on vähiten markkinariskiä aliarvioivia periodeja eri luottamustasoilla. EGARCH ja TGARCH -mallit suoriutuvat samalla mittarilla paremmin kuin muut GARCH - mallit. Kaikki mallit aliarvioivat historiallisiin arvoihin verrattuna liikaa markkinariskiä 99%, 95% ja 90%:n luottamustasoilla.
Keywords: Value at risk, VaR, GARCH, Bootstrapping, Market risk